Language promotion for refugees in VET: How to prepare vocational student teachers for a language-sensitive mentoring with refugees in apprenticeships? - Kimmelmann, Nicole (Pathways in Vocational Education and Training and Lifelong Learning. Proceedings of the 4th Crossing Boundaries Conference in Vocational Education and Training, Muttenz and Bern online, 8. - 9. April, 2021)
Context/Purpose: The paper summarizes evaluation results from a research project within a university mentoring program to support young refugees, during their apprenticeships in the German dual system, by a one-to-one mentoring program of vocational student teachers over a period of 2 years. Within this program, the mentors are qualified for their mentoring role in a modular course system. The paper addresses the embedded course, named “Language-sensitive mentoring”. The here described part of the project evaluation aims to identify didactical aspects that are critical for a successful preparation of vocational student teachers for a language-sensitive mentoring within a university course. Secondly, it examines how the University course change or influence language awareness and competences of mentors and how this interrelates with the design principles from their point of view. Approach: The course development is embedded in an iterative Design Based Research Cycle, incorporating three cohorts of mentors and courses. The paper presents consolidated design principles derived after two course executions with 43 mentors at all. Therefore, consequences of the first iteration are part of the comparative discussion. The derived design principles are based on a multi-method approach, combining questionnaires and open written reflections for mentors at the end of the course with retrospective notes of the course teachers. Results: The paper summarizes design principles derived from the data collection, structured along the categories “course program”, “course structure” and “course concept”. Challenging aspects for the course design are identified, in particular, as well as consequences for the final course design with the last cohort of mentors. Conclusions: The results demonstrate a high relevance of 1) a broad range of methods and practical materials brought into the course for individual testing of the mentors, 2) a continuous interconnections between the course and the mentoring via compulsory implementation tasks and 3) a regular common reflection of mentors` experiences of implementation phase integrated into the course concept.<br
Keywords: refugees; integrated content and language learning; mentoring; vocational student teachers; course design principles; Kulturelle Vielfalt